Modelling the growth and utilisation of kikuyu grass (Pennisetum clandestinum) under grazing. 2. Model validation and analysis of management practices - Herrero, Mario; Fawcett, R.H.; Dent, J.B. (Elsevier, 2000)
This paper presents validation results and some management applications of a Tropical Pasture Simulator. The e ects of di erent environmental conditions, N fertilisation regimes and grazing intensities are analysed, and physiological concepts are used to aid in the inter- pretation of the responses obtained. The model demonstrates the importance of ¯exible management guidelines depending on environmental conditions. It stresses the need for an increased understanding of the processes controlling the development and senescence of the sward, since these largely in¯uence the responses to nutrients and determine sward structure. Strategies based on morphological indicators such as number of live leaves were derived in order to develop simple and applicable pasture management guidelines at the farm level. Examples are presented with reference to kikuyu grass (Pennisetum clandestinum) production and utilisation in dairy systems in the highlands of Costa Rica.